Contribution to the genus Omalus Panzer, 1801 of China, with descriptions of two new species (Hymenoptera, Chrysididae) - Rosa, Paolo; Wei, Na-Sen; Xu, Zai-Fu (Zootaxa, 2015)
In spite of that Chinese species of the genus Omalus Panzer, 1801 were recently revised by Wei et al. (2014), the study of more material has revealed the presence of other four species: two of them are new, O. corrugatus Rosa, Wei & Xu, sp. nov. (China, Guangdong) and O. hainanensis Rosa, Wei & Xu, sp. nov. (China, Hainan); the other two are newly recorded from China, O. stella (Semenov & Nikol’skaya, 1954) and O. timidus (Nurse, 1902), comb. nov. (from the genus Holophris Mocsáry, 1890). An update key to Chinese species and illustrations are provided.